Indigenous African small ruminants: A case for characterisation and improvement - Rege, J.E.O. (International Livestock Centre for Africa, 1993)
The accelerating demands of a growing human population and the pressures of economic development are affecting the security and survival of many indigenous African breeds. Until now, these breeds have been a stable part of their particular ecosystems for hundreds of years. There is an increasing tendency to introduce exotic germplasm and/or to concentrate on a narrow range of supposedly more profitable breeds. As a result, indigenous breeds are threatened, even though they have been naturally selected for the local environments and are therefore best adapted. This paper describes the production systems in Africa and highlights the contribution of sheep and goats to subsistence farming systems and the general welfare of society. Problems preventing extensive utilisation and improvement of African animal genetic resources need to be identified. Genetic improvement programmes need to be developed. Breeds already endangered need to be conserved as a matter of urgency even if their economic value is not presently apparent. Concurrently, information should be compiled on biological performance and adaptive characteristics of these AGR (animal genetic resource) populations to aid the development of rational utilisation and conservation programmes.